A Study of the Effectiveness of Tin on the Thermal Conductivity Coefficient and Electrical Resistance of Se60Te40-xSnx Chalcogenide Glass - Khudhair, Nawal H.; Jasim, Kareem A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This research calculated the effect of partial replacement of Trillium with tin by weight ratios x=0, 5, 10, 15, and 20 of the weight of manufactured samples on the thermal conductivity coefficient of Se60Te40-xSnx chalcogenide glasses. The thermal conductivity coefficient of the samples was calculated using a disk- Lee. The results showed that increasing the concentration of tin improves the thermal insulation ability by decreasing the thermal conductivity value and then determining the optimal weight ratios at which a large thermal insulation is obtained. The electrical resistivity as a function of temperature was studied. The electrical resistivity (rd.c) was calculated as a function of temperature for all samples, using two-point probe techniques in the dark electrical resistivity measurements of Se60Te40-xSnx glasses for all values made in the temperature range 303-455 K. The electrical resistivity was found that it depends on the change in Tin addition, the temperature is clearly affected by the increase in the concentration of tin in the alloy. The electrical resistance increases when the concentration of Tin increase of Se60Te40-xSnx